(untitled) (Global Journal of Human-Social Science, 2021)
Foreign Language anxiety is a specific type of anxiety that accompanies the process of foreign language learning that can change according to a variety of variables such as the teacher- students relationship language attitudes and learning environment The purpose of this study was to examine the potential relation between students foreign language anxiety levels and learning environments traditional or distance learning in a university setting Faculty of arts and letters Fes Sais Morocco Students showed higher levels of anxiety within the distance learning setting compared to traditional education A survey using a 5 point Likert scale was employed Semi-structured interviews were also adapted The results indicated a significant increase in Communication apprehension test anxiety and fear of negative evaluation in distance learning compared to face to face setting The factors behind this have been questioned and analyzed The current study concludes with the current study s limitations as well as suggestions for further future research